The Physiological Effects of Stress Induced by the Distraction of a Ringing Cell Phone - Bowler, Bill; Bratberg, Lyndsey; Cavaleri, Hannah; Lorge, Amanda; Pitiger, Jamie (Journal of Advanced Student Sciences (JASS), 2015)
Stress in everyday life is associated with many adverse health effects. A variety of studies have explored specific triggers for a stress response, and have identified cell phone use as a potential cause of stress. The objective of this study was to observe the stress response caused by a cell phone ringing while taking a written multiple choice test. The subjects of the study were young adults. The test served as a distraction from each participant’s cell phone by requiring the participant to focus their attention on the test questions. During the test, electrodermal activity (EDA), heart rate, and respiration rate were recorded. It was hypothesized that there would be an increase in EDA, heart rate and respiration rate when a subjects’ personal cell phone rang while they were focused on completing the test. The data displayed a statistically significant increase in EDA activity after the phone rang, however; a significant increase was not observed in heart rate or respiration rate. Overall, the results of this study suggest that there is a significant physiological stress response to the distraction of a ringing cell phone when measured in terms of EDA.
An article that appeared in JASS, issue 2015
Keywords: auditory; cell phone; electrodermal activity (EDA); distraction; stress; heart rate; respiration rate